Cytokine profiling of pancreatic fluid using the ePFT collection method in tandem with a multiplexed microarray assay - Paulo, Joao A.; Lee, Linda S.; Wu, Bechien; Banks, Peter A.; Steen, Hanno; Conwell, Darwin L. (Journal of immunological methods, 2011)
Cytokines are secreted immunomodulating proteins involved in pancreatic stellate cell activation and propagation of fibrosis in chronic pancreatitis. We aim to show that cytokines can be identified from pancreatic fluid by (1) collecting pancreatic fluid with the ePFT method, (2) processing the fluid for cytokine-targeted microarray analysis, and (3) comparing cytokine profiles in pancreatic fluid of chronic pancreatitis (CP) patients and of chronic abdominal pain (CAP) controls. We endoscopically collected pancreatic fluid from patients with CP and those with CAP using the ePFT method. This fluid was subjected directly to a multiplexed cytokine protein microarray assay. Six patients (3 CP, 3 CAP) underwent a secretin-stimulated ePFT. The mean peak bicarbonate concentrations [meq/L] of the CP and CAP patients were 43 and 97, respectively. Statistically significant decreases in the cytokine concentrations of EGF, IP-10, eotaxin, IL-3, MIP-1a, IL-15, PDGF-AB/BB, and IL-1a were observed in the CP specimens (p < 0.05). We have successfully identified differences in the abundance of cytokines in ePFT-collected pancreatic fluid with a multiplexed microarray assay comparing CP and CAP controls. Further targeted investigation of cytokines in ePFT-collected fluid will broaden our knowledge of pancreatic immune response and pathogenesis in chronic pancreatitis. ► We have identified cytokines in pancreatic fluid using ePFT collection in tandem with cytokine microarray technology. ► Cytokines were differentially abundant in the pancreatic fluid of chronic pancreatitis and chronic abdominal paincohorts. ► We observed decreases in concentrations of EGF, IP-10, eotaxin, IL-3, MIP-1a, IL-15, PDGF-AB/BB, and IL-1a in CP specimens.